Implementasi Putusan PKPU Oleh Pengadilan Niaga terhadap Pihak yang Masih dalam Sengketa Keperdataan - Christian, Ronald; Hasibuan, Fauzie Yusuf; Hakim, Nur (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This thesis aims to: 1) Analyze and examine the legal basis of the Commercial Court in deciding Suspension of Debt Payment Obligation (PKPU) cases involving debtors still engaged in civil disputes in the District Court. 2) Analyze and examine the legal certainty for debtors whose PKPU is granted, particularly regarding agreements still subject to civil disputes outside the PKPU process. This study employs normative legal research, connecting the research with prevailing laws and regulations. The findings of this thesis are: 1) The judicial considerations in Decision No. 45/Pdt.Sus-PKPU/2023/PN Niaga Mdn embrace the principle of simple proof despite the complexity of debts involved in civil disputes. This decision demonstrates that, unlike bankruptcy, PKPU aims for swift debt restructuring and peaceful settlement. This is reflected in the judge's rejection of in personam disqualification and absolute competence exceptions, alongside the affirmation of the